Evaluasi Desain Struktur Pondasi Pada Pembangunan Gedung Masjid Proyek Medan Islamic Center - Rina Firlia Sari; Simon Dertha; Oloan Sitohang (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
The foundation planning of a building structure must consider several things, including the condition of the project area, soil type, and the type of foundation to be used. The foundation is a substructure system used to channel the load of the upper structure to the soil and hard rock layers. This study aims to evaluate the bearing capacity and settlement of the foundation of the Medan Islamic Center Mosque Building. This study is a qualitative study, collecting soil data by conducting soil investigations at the project site to determine the level of soil density, soil layer structure, soil classification and soil parameters. Then by means of documentation of data collection from several sources related to foundation data which are then analyzed by modeling close to the actual conditions using PLAXIS V.8.6 software. The results of this study indicate that the depth of the foundation ranges from 20.50 to 46 m and long-term settlement is up to 12 cm, so that supervision of the upper structure is needed. To reduce settlement, the use of friction piles is proposed.